A nationwide analysis of 16 year trends in cardiac transplantation for cardiac sarcoidosis. (25th November 2020) - Isath, A; Perembeti, S; Correa, A; Chahal, A; Padmanabhan, D; Rao, S; Garg, V; Contreras, J
Abstract: Background: Orthotopic heart transplant (OHT) is indicated for end-stage heart failure due to cardiac sarcoidosis (CS). However, utilization of OHT for CS has been controversial due to concern for involvement of other organs by sarcoidosis affecting long term outcomes. Purpose: Our objective was to study the trends in OHT in patients with CS in the United States using Healthcare Cost and Utilization Project (HCUP) National (nationwide) Inpatient Sample (NIS) from 1999 to 2014. Methods: Using NIS data, we identified patients older than 18 years with cardiac sarcoidosis using codes ICD 9-CM codes of 135 and 425.8. Among these patients, we identified those who underwent cardiac transplantation using ICD 9-CM procedure codes 37.5 and 33.6. We presented categorical data as percentages and continuous data as mean or median as appropriate. Results: A weighted total of 24231 hospitalizations for CS was extracted from 1999 to 2014 of which 248 (1.02%) CS patients underwent OHT. The trends in cardiac transplant for CS is as shown in Figure 1. The mean age of CS patients undergoing OHT was 51.7±1.1 years and 60.4% (n=150) were males. 114 (45.9%) were Caucasians and 27.8% (n=25) were African-American. 100% of the transplants were performed at medium (n=5) or large sized (n=243) teaching hospitals and 97.9% of cardiac transplants were also done at teaching hospitals. Heart transplants were mostly done in the South (36.3%) followed by Midwest (26.2%), West (25%) and Northeast (12.5%). Private insurance was the major payor source which covered 149 (60.1%) patients followed by Medicare covering 65 (26.2%) patients. A total of 10 (3.9%) cardiac sarcoidosis patients died during the same hospitalization for cardiac transplantation. Following OHT, 84.2% (n=209) were discharged home and 11.6% (n=29) to short term hospitalization. The mean cost of hospitalization for OHT in CS when adjusted for inflation was 535144±56060 dollars while the average length of stay for heart transplant for CS was 46.2±6.6 days. Conclusions: Cardiac transplant trends in CS have not changed from 1999 to 2014 despite recent studies showing improved outcomes and are associated with substantial cost of hospitalization and length of stay. Majority of cardiac transplant was done in Caucasians despite cardiac sarcoidosis being more common in African-Americans. Funding Acknowledgement: Type of funding source: None